Wharton’s jelly mesenchymal stromal cells derived from preterm umbilical cord reveal a hepatogenic potential - F. Timoneri; M. Lo Iacono; S. Corrao; G. Alberti; G. Amico; T. Corsello; P. G. Conaldi; Eleonora Russo; Eleonora Russo; G. La Rocca (Frontiers in Cell and Developmental Biology)
IntroductionThe umbilical cord (UC) is a perinatal tissue from which it is possible to isolate mesenchymal stromal cells (MSCs) with a higher proliferation rate and a higher differentiation capacity compared to their adult counterparts. Wharton’s jelly (WJ) is a rich source of multipotent and hypoimmunogenic MSCs (WJ-MSCs), which are considered promising candidates for cell therapy of many conditions, including liver diseases. Preterm umbilical cord (birth before 37 weeks of gestation) is generally considered a waste product, so its use does not affect ethical issues. Similarly to the full-term UC, it can be considered a valid source of WJ-MSCs, although little is known about their phenotype and differentiation capacity. We aim to show that WJ-MSCs derived from preterm umbilical cords exhibit comparable characteristics to their mature counterparts and, in particular, show a similar ability to differentiate into hepatocyte-like cells and retain hypoimmunogenicity features. Both these aspects may be key in the prospective application of these cells in regenerative medicine.Material and MethodsHere, we isolated WJ-MSCs from seven prematurely harvested umbilical cords (pWJ-MSCs). We assessed a mesenchymal phenotype and differentiation potential by flow cytometry, immunocytochemistry, and immunofluorescence. A standardized liver differentiation protocol was performed, and the acquisition of the hepatic phenotype was assessed by characterization of hepatic protein expression and functional assays.ResultsWe demonstrated that pWJ-MSCs exhibited mesenchymal characteristics, acquired phenotypical and functional features of hepatocytes when induced to differentiate in a specific medium, and maintained the expression of immunomodulatory molecules.DiscussionThis study showed that even if pregnancy has been interrupted before the 22nd week, p-WJ-MSCs had the same differentiative ability as the counterpart derived from the full-term UC, that we have previously demonstrated, and can be considered a valid cellular population for liver cell therapy.